Initial Experience with p64: A Novel Mechanically Detachable Flow Diverter for the Treatment of Intracranial Saccular Sidewall Aneurysms - Fischer, S.; Aguilar-Pérez, M.; Henkes, E.; Kurre, W.; Ganslandt, O.; Bäzner, H.; Henkes, H. (American Journal of Neuroradiology, 2015)
BACKGROUND AND PURPOSE: Flow diverters are important tools for the treatment of intracranial aneurysms. We report a retrospective evaluation of the safety and efficacy of p64, a fully resheathable, detachable flow diverter, in the endovascular treatment of intracranial sidewall aneurysms.MATERIALS AND METHODS: Results of 121 patients with 130 aneurysms (median neck size, 3 mm; median fundus size, 4 mm), treated from April 2012 through October 2014, were analyzed. Aneurysms were unruptured or beyond the acute SAH phase. Thirteen aneurysms were located in the posterior circulation. Twenty-three aneurysms had previous saccular treatment but no previous parent vessel stent placement. In 19 aneurysms, a combination of coiling and flow diversion was performed.RESULTS: Successful p64 deployment was achieved in 127/130 aneurysms. The average number of p64s used was 1.1 per aneurysm. The rates of transient and permanent morbidity and mortality were 5%, 1.7%, and 0.8%, respectively. Three-month DSA follow-up in 123/130 aneurysms showed complete occlusion in 58.5%. Nine-month DSA follow-up in 93/106 (87.7%) eligible aneurysms showed complete occlusion in 79.6%. Late follow-up (median, 496 days) has already been performed in 35 aneurysms, showing complete occlusion in 30 (85.7%).CONCLUSIONS: p64 offers an efficacious treatment option for intracranial sidewall aneurysms with a high aneurysm occlusion and an acceptable complication rate. The possibility of repositioning or removing the device was an advantage. The higher attenuation may lead to fewer devices per case and early aneurysm occlusion. Long-term follow-up data are pending.LLlumen lossPEDPipeline Embolization Device